Introductory Speech - Justice and the Post Crash Response - Ramos, M. (Justice and the Post Crash Response - Side event of the 2nd High-Level Conference on Road Safety - Brasilia, 2015)
The Post-Crash Response is the fifth pillar of the UN’s Decade of Action Road Safety Plan (DOA RSP). The other four pillars are road safety management, safer roads and mobility, safer vehicles, and safer road users. The DOA RSP was launched in May 2011, with Pillar 5: Post-Crash Response having seven activities, which are summarized as: 1. Develop prehospital care systems. 2. Develop hospital trauma care systems and evaluated the quality of care. 3. Provide early rehabilitation and support to injured patients and those bereaved by road traffic crashes, to minimize both physical and psychological trauma. 4. Encourage the establishment of appropriate road user insurance schemes. 5. Encourage a thorough investigation into the crash and the application of an effective legal response. 6. Provide encouragement and incentives for employers to hire and retain people with disabilities. 7. Encourage research and development into improving post-crash response